Romero-González, Dámaris, Israel Muñoz Gallarte, y G. Laguna Mariscal (eds.), Visitors from Beyond the Grave: Ghosts in World Literature, Coimbra, Imprensa da Universidade da Coimbra, 2019, 300 pp. (Estudios Humanísticos. Filología, 2021)
Reseña